Multinutrient block handbook - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Multinutrient block handbook by L Garcia and J Restrepo 1995 28pp ISBN 92 5 103617 9